The Not-So-Dark Side of Materialism: Can Public Versus Private Contexts Make Materialists Less Eco-Unfriendly? - Wang, Luxiao; Gu, Dian; Jiang, Jiang; Sun, Ying (Frontiers in Psychology, 2019)
Materialism, a way of life characterized by pursuing possessions, image and status, has always been looked upon as self-interested and unkind. Previous studies have widely verified that materialism has a negative impact on individuals’ pro-environmental behaviors. The present research focused on whether the public (versus private) nature of a decision context will make materialists behave in less eco-unfriendly ways. In Study 1, the behavioral decision context (public vs. private) was manipulated to examine whether the relationship between materialism and pro-environmental behaviors would vary as a function of the situation. In Study 2, we manipulated materialism and contexts simultaneously to verify the hypothesis again. Findings in the two studies consistently revealed that public versus private contexts played a moderating role between materialism and pro-environmental behaviors. That is, in private, individuals with higher levels of materialism were less eco-friendly than those with lower levels of materialism, but the negative effect disappeared in public. We concluded with a discussion of the theoretical and practical implications of the research findings.